EDUCATION ASSISTANCE POLICY OF THE FAMILY HOPE PROGRAM ON THE WELFARE OF THE PEOPLE OF SALENRANG VILLAGE, BONTOA DISTRICT, MAROS REGENCY - Risnawati, Eka; Guntur, Muhammad; Yamin, Muh. Nur (Jurnal Aktor, 2025)
Policy on Assistance Educational for the Family Hope Program for the Welfare of the People of Salenrang Village, Bontoa District, Maros Regency. Thesis. Faculty of Social Sciences and Law, Makassar State University. Supervised by Muhammad Guntur and Muh. Nur Yamin. This study aims to determine how much the Family Hope Program's educational assistance influences the welfare of the people of Salenrang Village, Bontoa District, Maros Regency. In achieving the research objectives, the researchers used data collection techniques through observation, questionnaires (questionnaires), and documentation. The data that was obtained from the research results were then processed using quantitative analysis to find out that the educational assistance of the Family Hope Program had an influence on the welfare of the people of Salenrang Village, Bontoa District, Maros Regency. The research results show that: (1). The policy of educational assistance for the Family Hope Program in Salenrang Village, Bontoa District, Maros Regency shows that the nine indicators evaluating activities for the distribution of educational assistance for the Family Hope Program, namely availability, relevance, affordability, utilization, coverage, quality, effort, efficiency, and impact can be realized in the distribution educational assistance for the family of hope program in Salenrang Village, Bontoa District, Maros Regency. (2). The welfare of the people of Salenrang Village, Bontoa District, Maros Regency shows that the four indicators of community welfare, namely the ability to survive, education, consumption level or pattern, as well as housing and the environment can be realized due to the distribution of educational assistance for the family of hope program in Salenrang Village, Bontoa District, Maros Regency. (3). There is a significant influence between the educational assistance of the family hope program on the welfare of the people of Salenrang Village, Bontoa District, Maros Regency, namely with the value of the coefficient of determination R2 of 0.624 or equal to 62.4%.